The Aquatic Symbiosis Genomics Project: probing the evolution of symbiosis across the Tree of Life [version 2; peer review: 4 approved, 1 approved with reservations] - Matthew Berriman; Victoria McKenna; Roxanne Beinart; John M. Archibald; Ute Hentschel; Michael N. Dawson; Jose V. Lopez; Patrick J. Keeling; Jillian M. Petersen; Mark Blaxter; José M. Martín-Durán; Oleg Simakov; et al. (Wellcome Open Research)
We present the Aquatic Symbiosis Genomics Project, a global collaboration to generate high quality genome sequences for a wide range of eukaryotes and their microbial symbionts. Launched under the Symbiosis in Aquatic Systems Initiative of the Gordon and Betty Moore Foundation, the ASG Project brings together researchers from across the globe who hope to use these reference genomes to augment and extend their analyses of the dynamics, mechanisms and environmental importance of symbioses. Applying large-scale, high-throughput sequencing and assembly technologies, the ASG collaboration will assemble and annotate the genomes of 500 symbiotic organisms – both the “hosts” and the microbial symbionts with which they associate. These data will be released openly to benefit all who work on symbioses, from conservation geneticists to those interested in the origin of the eukaryotic cell.